Legionella indianapolisensis sp. nov., isolated from a patient with pulmonary abscess. (April 2018) - Relich, R.F.; Schmitt, B.H.; Raposo, H.; Barker, L.; Blosser, S.J.; May, M.
Highlights: The article entitled " Legionella indianapolisensis sp. nov., isolated from a patient with pulmonary abscess" describes the detection and identification of a novel human-pathogenic Legionella species isolated from a bronchoalveolar lavage fluid specimen from a patient with pulmonary abscess and a recent history of influenza. This manuscript reviews the methods used for characterization of this novel organism, as well as its phylogenetic comparison based on 16S rRNA gene sequencing. Abstract: Background: To date, at least 50 species of Legionella have been described. These organisms are ubiquitous in nature and have been isolated from diverse ecological environments, including man-made structures such as cooling towers and spas. Legionellae have also been isolated from human and veterinary clinical specimens, and their roles in disease are well-established. This report describes the isolation of a novel Legionella species from a respiratory specimen from a patient with influenza and suspected pulmonary embolus. Case: A 68-year-old male presented to an Indianapolis-area hospital with pulmonary disease; upon workup, he was found to have influenza A. Bronchoalveolar lavage fluid was also submitted for conventional bacterial culture and Legionella culture. The patient was prescribed a broad-spectrum antibiotic and recovered. Results: A Legionella -like bacterium was isolated on buffered charcoal yeast extract agar, and mass spectrometry and comparative 16S rRNA gene sequencing inconclusively identified the isolate as a Legionella sp. Further analysis of the 16S rRNA gene confirmed the strain to be a new species, related to Legionella hackeliae . Physiochemical and morphological testing were used to confirm the discovery of a novel species, Legionella indianapolisensis sp. nov., type strain SMNF-IS.